Analysis Of Product Quality, Price, Service Quality, Promotion And Place On Customer Loyalty And Customer Satisfaction Special Sambal (SS) Samirono Branch And Yogyakarta Veterans - Agus imam; Hwihanus Hwihanus; Muhammad Bayu; Darmono Darmono (International Journal of Economics, Business and Innovation Research, 2023)
In the era of globalization, this is what has happened to the development of the restaurant and restaurant business. Now the paradigm of restaurants and restaurants has changed, which previously only provided a menu of dishes (food and drinks) for sale but has now become a modern concept that offers a variety of services. In addition to satisfying the hunger of customers, restaurant and restaurant businesses also provide a comfortable, calm atmosphere in eating dishes. The level of consumer satisfaction with an item or service will reflect the company's level of success in marketing its products. A product or service will fail if it cannot provide satisfaction to consumers. However, efforts to satisfy consumers are very difficult because competition is so intense and changes in the social environment affect consumer behavior and the rate of economic growth is getting higher. The purpose of this study is to obtain in-depth knowledge and description and provide empirical evidence regarding product quality, price, service quality, promotion and location on customer loyalty and customer satisfaction at Stall SS (Special Sambal): The type of research used in this study is causal associative research because it analyzes causal relationships, namely the independent variable (X) affects the dependent variable (Y). The approach used in this research is a quantitative approach. The quantitative approach is research that uses numbers, starting from data collection, interpretation of the data, and the appearance of the results. The results of this study indicate that (1) there is no positive effect of product quality on customer satisfaction with special chili sauce (SS). (2) There is a positive effect of price on special chili sauce (SS) customer satisfaction. (3) There is a positive effect of service quality on special chili sauce customer satisfaction (SS). (4) There is a positive effect of promotion on customer satisfaction (SS). (5) there is a positive effect of place on customer satisfaction (SS). (6) there is a positive influence of product quality, price, place, promotion, customer satisfaction on customer loyalty (SS).